Qualitative Analysis of the Determinants of Malnutrition among Children Under-five in Households in the Mayo-Danay Division, Cameroon - André Izacar Gaël Bita; Benjamin Azike Chukuwchindun; Thomas Eddy Biwole Omgba; Agbor Nyenty Agbornkwai; Justin Bienvenu Eyong; Martin Sobze Sanou (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
The Far North region has the highest rate of chronic malnutrition (35.9%) ahead of East (35.4%); North (30.6%) and Adamawa (28.7%). The study aimed to identify contextual factors of child malnutrition in line with UNICEF’s causal pattern of malnutrition (2013). This was a qualitative study. Multiple case sampling of social micro-units was used. Focus-groups; face-to-face interviews and observations were organized. Seguin method was used for data analysis (2010). Fifty people participated in the study. Mayo-danay is a landlocked area, where the lack of food processing and food conservation infrastructure promotes early and low-cost liquidation of food products. A situation that exposes families to famine and poverty a few months after the harvest. The influx of internally displaced persons (IDPs); insecurity due to terrorism has weakened cross-border trade. The household size is up to 10 members, that did not allow children to eat at their convenience, and in a diverse way. The Christian head of households did not systematically contribute to the food ration, unlike the Muslims. Fish, agricultural and livestock products are more for sale than for consumption in the household. There are frequent shortages of food supplements for the management of malnutrition in health training. The causes of malnutrition in Mayo-Danay were multifactorial. Strategies to fight against malnutrition must take into account the integrated approach to local and sustainable development.